Association Between Absolute Neutrophil Count and Variation at TCIRG1: The NHLBI Exome Sequencing Project. Issue 6 (27th May 2016) - Rosenthal, Elisabeth A.; Makaryan, Vahagn; Burt, Amber A.; Crosslin, David R.; Kim, Daniel Seung; Smith, Joshua D.; Nickerson, Deborah A.; Reiner, Alex P.; Rich, Stephen S.; Jackson, Rebecca D.; Ganesh, Santhi K.; Polfus, Linda M.; et al.
ABSTRACT: Neutrophils are a key component of innate immunity. Individuals with low neutrophil count are susceptible to frequent infections. Linkage and association between congenital neutropenia and a single rare missense variant in TCIRG1 have been reported in a single family. Here, we report on nine rare missense variants at evolutionarily conserved sites in TCIRG1 that are associated with lower absolute neutrophil count (ANC; p = 0.005) in 1, 058 participants from three cohorts: Atherosclerosis Risk in Communities (ARIC), Coronary Artery Risk Development in Young Adults (CARDIA), and Jackson Heart Study (JHS) of the NHLBI Grand Opportunity Exome Sequencing Project (GO ESP). These results validate the effects of TCIRG1 coding variation on ANC and suggest that this gene may be associated with a spectrum of mild to severe effects on ANC.